Altered soluble epoxide hydrolase-derived oxylipins in patients with seasonal major depression: An exploratory study. (June 2017) - Hennebelle, Marie; Otoki, Yurika; Yang, Jun; Hammock, Bruce D.; Levitt, Anthony J.; Taha, Ameer Y.; Swardfager, Walter
Abstract: Many cytochrome p450-derived lipids promote resolution of inflammation, in contrast to their soluble epoxide hydrolase(sEH)-derived oxylipin breakdown products. Here we compare plasma oxylipins and precursor fatty acids between seasons in participants with major depressive disorder with seasonal pattern (MDD-s). Euthymic participants with a history of MDD-s recruited in summer-fall were followed-up in winter. At both visits, a structured clinical interview (DSM-5 criteria) and the Beck Depression Inventory II (BDI-II) were administered. Unesterified and total oxylipin pools were assayed by liquid chromatography tandem mass-spectrometry (LC-MS/MS). Precursor fatty acids were measured by gas chromatography. In nine unmedicated participants euthymic at baseline who met depression criteria in winter, BDI-II scores increased from 4.9±4.4 to 19.9±7.7. Four sEH-derived oxylipins increased in winter compared to summer-fall with moderate to large effect sizes. An auto-oxidation product (unesterified epoxyketooctadecadienoic acid) and lipoxygenase-derived 13-hydroxyoctadecadienoic acid also increased in winter. The cytochrome p450-derived 20-COOH-leukotriene B4 (unesterified) and total 14(15)-epoxyeicosatetraenoic acid, and the sEH-derived 14, 15-dihydroxyeicostrienoic acid (unesterified), decreased in winter. We conclude that winter depression was associated with changes in cytochrome p450- and sEH-derived oxylipins, suggesting that seasonal shifts in omega-6 and omega-3 fatty acid metabolism mediated by sEH may underlie inflammatory states in symptomatic MDD-s. Highlights: Oxylipins are lipids that reflect regulation of inflammatory and resolution pathways. Soluble epoxide hydrolase (sEH) produces oxylipins that are less anti-inflammatory. sEH derived oxylipins fluctuated between mood states in seasonal depression. sEH activity may underlie inflammatory states in symptomatic seasonal depression. This lipidomic assay offers new potential for standardized quantitative biomarkers.